Demystifying a hexuronic acid ligand that recognizes Toxoplasma gondii and blocks its invasion into host cells. Issue 18 (17th April 2019) - Subramani, Balamurugan; Shantamurthy, Chethan D.; Maru, Parag; Belekar, Meenakshi A.; Mardhekar, Sandhya; Shanmugam, Dhanasekaran; Kikkeri, Raghavendra
Abstract : Toxoplasma gondii is a ubiquitous eukaryotic pathogen responsible for toxoplasmosis in humans and animals. Abstract : Toxoplasma gondii is a ubiquitous eukaryotic pathogen responsible for toxoplasmosis in humans and animals. This parasite is an obligate intracellular pathogen and actively invades susceptible host cells, a process which is mediated by specific receptor–ligand interactions. Here, we have identified an unnatural 2, 4-disulfatedd -glucuronic acid (Di-S-GlcA), a hexuronic acid composed of heparin/heparan sulfate, as a potential carbohydrate ligand that can selectively bind to T. gondii parasites. More importantly, the gelatin conjugated Di-S-GlcA multivalent probe displayed strong inhibition of parasite entry into host cells. These results open perspective for the future use of Di-S-GlcA epitopes in biomedical applications against toxoplasmosis.